Pros and Cons of the Globalization of the World Economy Impact on the Development of Accounting - E. A. Sharovatova (Учёт. Анализ. Аудит, 2020)
The globalization of the modern economy imposes special requirements on national accounting systems with the focus on standardization of information summarizing methods in order to form unified accounting statements. Public companies seeking to become players on the global trade platform are forced to adopt the rules of the international accounting and reporting. This has certain implications for national accounting in different countries. The article offers a study of the alternative influence of the phenomenon of economic globalization on the development of modern accounting. Positive and negative factors of such influence which have already forever changed the quality of the accounting, (Russia included), are highlighted, meaning not only improvement of the methods of accounting information generalization but also changes in the very attitude to the accounting profession. It is concluded that the consequences of economic globalization for the countries participating in the world trade platform have led to a positive change in the quality of the accounting system as a whole. However, to maintain this trend, the participation of educational institutions and professional communities along with the state in the improvement of an accounting process is required.